The Allocation of Committee Chairs and the Oversight of Coalition Cabinets in Belgium. Issue 1 (23rd January 2023) - Chiru, Mihail; De Winter, Lieven
Abstract: The appointment of committee chairs to monitor the actions of ministers belonging to coalition partners has received considerably less attention than other mechanisms of policing the coalition agreement at executive or legislative level. We take a longitudinal perspective focusing on 11 Belgian cabinets (1980–2018) to study the determinants of such appointments and whether there is a substitution effect between shadow chairs, junior ministers and coalition agreements. Our findings indicate that the probability of appointing a shadow committee chair is higher when the ideological distance between the minister's party and the coalition is larger. Other key findings are that ministers facing hostile junior ministers tend to be shadowed by committee chairs as well, while shadow chairs are also more frequent in minimum winning coalitions.